Repercussões do trabalho na saúde dos servidores dos campi avançados do IFMA - TROVÃO, Renata Cardoso (2023)
With the advent of the capitalist mode of production, the transformations in work were profound. Currently, there is a huge precariousness of work with loss of labor rights, high unemployment and informality rates, weakening of labor collectives, increased competitiveness and work intensification. This context of precariousness has also strongly affected the public service. The liberal project that defends the diminution of the State has led to the privatization of public institutions and cuts in the budget. In addition, the image of public servants has been heavily attacked, leading to a revulsion on the part of the population towards public institutions. In recent years, public education has suffered intensely from this political model. Another important fact, in this scenario, is the advent of the managerial model of management in public institutions, which has brought changes to the organization and working conditions. In this context, public educational institutions have been strongly affected by all these aspects. The Federal Institute of Education, Science and Technology of Maranhão (IFMA) is one of these educational institutions that has been experiencing such impacts. IFMA has 29 campuses spread across all regions of Maranhão. Three of these campuses are of the advanced campus typology, whose structure differs from the other campuses by prioritizing the provision of technical and short-term courses and continuing education, as they are administratively linked to another campus or to the Rectory and because they have a reduced staff. Bearing in mind the specificities of this type of campus, this dissertation proposed carrying out a research that aimed to analyze the repercussions of work on the health of servers at the advanced campuses of IFMA, located in the cities of Carolina, Porto Franco and Rosário. The theoretical basis adopted was the Psychodynamics of Work in articulation with Historical-Dialectic Materialism. As for the method, a qualitative research was carried out, in which eighteen servants were interviewed, including administrative technicians in education, teachers and general directors of the three campuses. To analyze the data collected in the empirical research, Critical Discourse Analysis, proposed by Norman Fairclough, and Historical-Dialectic Materialism were used. The results found showed that the working conditions and the organization of work on the advanced campuses of the IFMA have led to great suffering for most of the servants interviewed. The lack of adequate infrastructure and materials, as well as the low number of servers, are among the factors that generate the most difficulty in the work.